2022
DOI: 10.3390/membranes12070701
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Eco-Friendly Packaging Films Based on Poly (Vinyl Alcohol) and Glass Flakes

Abstract: The majority of food packaging materials are petroleum-based polymers, which are neither easily recyclable nor ecologically friendly. Packaging films should preferably be transparent, light in weight, and easy to process, as well as mechanically flexible, and they should meet the criteria for food encapsulation. In this study, poly (vinyl alcohol) (PVA)-based films were developed by incorporating glass flakes into the films. The selection of PVA was based on its well-known biodegradability, whereas the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Water and moisture present in the soil diffused into the films, causing them to expand, which resulted in improved biodegradability. The results of the present study are excellent as compared to the previous studies which have shown degradation rates at 36 and 40%. ,, …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Water and moisture present in the soil diffused into the films, causing them to expand, which resulted in improved biodegradability. The results of the present study are excellent as compared to the previous studies which have shown degradation rates at 36 and 40%. ,, …”
Section: Resultssupporting
confidence: 82%
“…The results of the present study are excellent as compared to the previous studies which have shown degradation rates at 36 and 40%. 1,37,38 3.5. Wettability of Synthesized Films.…”
Section: Soil Burial Degradationmentioning
confidence: 99%
“…In addition, PVA films are also transparent, allowing consumers to see the food without compromising its integrity. Additionally, PVA is non-toxic and biodegradable, making it an environmentally friendly choice for food packaging [ 7 ]. PVA is used in a variety of medical and pharmaceutical applications due to its biocompatibility and ability to form hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…They are highly compatible with paper and effective at repelling grease, since they decrease porosity and are insoluble in non-polar solvents [ 8 ]. Nonetheless, their overall barrier properties are allegedly worse than those of poly(vinyl alcohol) (PVA), a synthetic but water-soluble and biodegradable polymer [ 9 ]. Desirable materials also include minerals that are found naturally and abundantly in soils and waters.…”
Section: Introductionmentioning
confidence: 99%